EVALUATION OF BIOCHEMICAL PARAMETERS IN FEMALE FISHER RATS SUBJECTED TO SWIMMING TRAINING IN DIFFERENT VOLUMES (30, 60, 120 AND 240 MINUTES). (Fiep Bulletin - online, 2011)
In the last years various researches have stressed how much physical activity has been efficient in the prevention and treatment of diseases. In the present work we studied the biochemical and nutritional  parameters which allow a general view of the benefits of exercise for the health of Fisher female rats subjected to swimming training in different volumes (30, 60, 120 and 240 minutes). Forty six animals were used which were divided into four groups with the cited volumes of exercise and one sedentary group, all fed commercial ration. Concerning the hepatic function there was an increase in total protein in groups T30`, T120` and T240`, an increase in alkaline phosphatase in group T120`, a decrease in AST in the T30` and an increase in ALT in the T240` animals. As for renal function creatinine was augmented in the T30` group in relation to the sedentary group and an increase in urea in groups T60`, T120` and T240` was observed. In lipid profile total cholesterol was found diminished in the trained animals. A decrease in creatine kinase in groups T60`, T120` and T240` and a decrease in lactic deshidrogenase in relation to the sedentary rats were also observed. Free sulphydrils were found decreased in animals of groups T120` and T240`. The present results have demonstrated the beneficial effects of training on biochemical parameters, improving the physical condition and generating a better adaptation in the LDH activity. Furthermore total cholesterol and its fractions were diminished. Good responses were also obtained in hepatic and renal functions.
Keywords: training; swimming; biochemical parameters